Post-traumatic Stress and Marijuana Outcomes: The Mediating Role of Marijuana Protective Behavioral Strategies - Jordan, Hallie R. (Subst Abus, 2019)
BACKGROUND: The present study investigated the mediating role of protective behavioral strategies for marijuana (PBSM) on the relationship between posttraumatic stress disorder (PTSD) and marijuana outcomes (i.e. marijuana use frequency, marijuana use quantity, cannabis use disorder (CUD) symptoms, and marijuana-related problems). METHODS: Participants were 1,107 traditional age college students (M(age) = 20.26, SD = 3.32; 66.5% White, non-Hispanic; 68.8% female), who reported consuming marijuana at least once in the last 30 days and completed measures of PTSD symptoms, PBSM, and marijuana-related outcomes. RESULTS: PBSM significantly mediated the positive relationships between PTSD symptoms and both CUD symptoms and marijuana-related problems. More specifically, PTSD symptoms were negatively associated with PBSM, which in turn was negatively associated marijuana use frequency and marijuana use quantity, which were in turn positively associated with CUD symptoms and marijuana-related problems. CONCLUSION: Taken together, the associations between higher PTSD symptoms and greater experience of CUD symptoms and marijuana-related problems may occur because students use fewer PBSM and thus engage in larger quantity and frequency of marijuana use. These findings lend support to the utility of targeting PBSM as a harm reduction effort for students with PTSD symptoms who use marijuana.